Left-sided paraduodenal hernia: Report of a case - YEGEN, ŞEVKET CUMHUR (SPRINGER, 2006)
Paraduodenal hernias are rare congenital malformations consisting of incomplete rotation of the midgut, which may lead to intestinal obstruction or simply be detected as an incidental finding at autopsy or laparotomy. We report a case of left paraduodenal hernia diagnosed preoperatively by computed tomography and operated on in an emergency setting for signs of peritoneal irritation. A misdiagnosis had been made when the patient suffered his first attack 6 months earlier and he had been treated for familial Mediterranean fever. We reduced the small bowel loops from the left paraduodenal hernia sac with ligation and transection of the inferior mesenteric vessels. The patient was discharged from hospital on postoperative day 4 after an uneventful recovery.
Keywords: paraduodenal hernia; abdominal pain; familial Mediterranean fever; FAMILIAL MEDITERRANEAN FEVER; SURGICAL-MANAGEMENT; INTERNAL HERNIA; CT FINDINGS; DIAGNOSIS; EMPHASIS